Iron Oxide–Modified Carbon Electrode and Sulfate-Reducing Bacteria for Simultaneous Enhanced Electricity Generation and Tannery Wastewater Treatment - Miran, Faiz; Mumtaz, Muhammad Waseem; Mukhtar, Hamid; Akram, Sadia (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial fuel cell (MFC) is emerging as a potential technology for extracting energy from wastes/wastewaters while achieving their treatment. The major hindrance in MFC commercialization is lower power generation due to the sluggish transfer of electrons from biocatalyst (bacteria) to the anode surface and inefficient microbial consortia for treating real complex wastewaters. To overcome these concerns, a traditional carbon felt (CF) electrode’s modification was carried out by iron oxide (Fe3O4) nanoparticles via facile dip-and-dry methods and mixed sulfate reducing bacteria (SRB) were utilized as efficient microbial consortia. In the modified CF electrode with SRB, a considerable improvement in the bioelectrochemical operation was observed; where the power density (309 ± 13 mW/m2) was 1.86 times higher compared to bare CF with SRB (166 ± 11 mW/m2), suggesting the better bioelectrochemical performance of a SRB-enriched Fe3O4@CF anode in the MFC. This superior activity can be assigned to the lower charge transfer resistance, higher conductance and increased numbers of catalytic sites of the Fe3O4@CF electrode. SRB enriched Fe3O4@CF anode also assist in enhancing the MFC performance in terms of COD removal (>75%), indicating efficient biodegradability of tannery wastewater and higher electron transfer rate from SRB to conductive anode. These findings demonstrate that a combination of the favorable properties of nanocomposites such as Fe3O4@CF anodes and efficient microbes for treating complex wastes can encourage new directions for renewable energy-related applications.